Comparison of Scheimpflug Derived Biomechanical and Tomographical Indices to Detect Corneal Ectasia - A Cross Sectional Study - Younis, Fazla; Zafar, Omar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare Corvis ST (Oculus Wetzlar, Germany) and Pentacam (Oculus) derived indices to detect normal cornea, keratoconus and for mefruste keratoconus.Study Design: Comparative cross sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi, from Feb to Jul 2019.Methodology: Following strict inclusion criteria 90 patients were enrolled that were divided into 3 equal groups of normal, Keratoconus and Formefruste kertoconus. One eye of the patient was selected and underwent ophthalmic examination followed by assessment of Corvis ST (Oculus Wetzlar, Germany) and Pentacam (Oculus). Classification analysis between normal, keratoconus and formefruste keratoconus was evaluated using receiver operating characteristic (ROC) curves. The area under the ROC curve (AUC) was compared.Results: Several corneal response parameters generated by Corvis St (Oculus Wetzlar, Germany) were statistically significant (p-value